Artificial Intelligence (AI) in Enhancing Spoken English Proficiency: A Systematic Literature Review - Mardhiah, Ainol; Diana Purwati; Lathifatuddini; Hayatul Muna; Helmiyadi (Universitas Veteran Bangun Nusantara, 2024)
This systematic review explores the integration of Artificial Intelligence (AI) tools in teaching spoken English to EFL learners, with an emphasis on intelligent tutoring systems, speech recognition applications, and technologies providing adaptive feedback. A comprehensive search of academic databases, primarily Google Scholar, initially identified 17,200 articles on AI in English learning. By applying Boolean techniques, this number was narrowed down to 45 articles specifically addressing AI tools for spoken English learning in Indonesia. After applying inclusion and exclusion criteria, 14 articles published in national and international journals, were chosen for further review. A qualitative analysis of these studies revealed key themes such as the benefits of AI tools in enhancing students’ spoken English proficiency and challenges in implementation. The review highlights emerging trends, identifies research gaps, and offers recommendations for optimizing AI-driven approaches in EFL contexts. The findings emphasize AI's potential to enhance spoken English proficiency while also underscoring areas that require further attention to optimize their application. Effective strategies for integrating AI tools with instructional practices should be examined in future research to optimize learner engagement and enhance spoken English proficiency.